A Dual‐Responsive Magnetoactive and Electro–Ionic Soft Actuator Derived from a Nickel‐Based Metal–Organic Framework (Adv. Mater. 35/2022). Issue 35 (1st September 2022) - Mahato, Manmatha; Hwang, Won‐Jun; Tabassian, Rassoul; Oh, Saewoong; Nguyen, Van Hiep; Nam, Sanghee; Kim, Ji‐Seok; Yoo, Hyunjoon; Taseer, Ashhad Kamal; Lee, Myung‐Joon; Zhang, Huapeng; Song, Tae‐Eun; et al.
Abstract : Dual‐Responsive Actuators In article number 2203613, Il‐Kwon Oh and co‐workers report the design and synthesis of magnetically and electrically driven dual‐responsive soft actuators (MESAs) from a nickel‐based metal–organic framework. The MESA is successfully utilized to demonstrate the hovering motion of a hummingbird robot under magnetic and electric fields.